2018
DOI: 10.31557/apjcp.2018.19.12.3353
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL-10 rs1800871 and rs1800872 Polymorphisms with Breast Cancer Risk: A Systematic Review and Meta-Analysis

Abstract: Background: The rs1800871 and rs1800872 polymorphisms of interleukin 10 (IL-10) gene has been indicated to be associated with breast cancer (BC) risk, but study results are still debatable. To derive a more precise evaluation, we performed a comprehensive meta-analysis. Methods: Multiple electronic databases were searched to identify studies assessing the IL-10 rs1800871 and rs1800872 polymorphisms with BC risk. Results: A total of 21 case-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 24 publications
0
24
0
1
Order By: Relevance
“…In contrast, multivariate analysis demonstrated that a higher IL-10 level is associated with worse disease conditions, including late-stage, ER-negative, and PR-negative breast cancer in our study. A systematic review and meta-analysis revealed that the rs1800871 and rs1800872 polymorphisms of the IL-10 gene are associated with overall breast cancer risk in the general population [ 25 ]. We speculate that IL-10 expression in breast cancer may serve as a preferential metastatic condition that permits cells to evade host anticancer immunity, which is dependent on the ER and PR status.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, multivariate analysis demonstrated that a higher IL-10 level is associated with worse disease conditions, including late-stage, ER-negative, and PR-negative breast cancer in our study. A systematic review and meta-analysis revealed that the rs1800871 and rs1800872 polymorphisms of the IL-10 gene are associated with overall breast cancer risk in the general population [ 25 ]. We speculate that IL-10 expression in breast cancer may serve as a preferential metastatic condition that permits cells to evade host anticancer immunity, which is dependent on the ER and PR status.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 38 ] It has been reported that polymorphisms in the promoter region of IL-10 may influence the production of IL-10. [ 39 ] There are many studies and systematic analyses reporting the association between SNPs of IL-10 and other cancers, including gastric cancer40, [ 40 ] cervical cancer, [ 41 ] breast cancer, [ 42 ] and prostate cancer. [ 43 ]…”
Section: Discussionmentioning
confidence: 99%
“…After meta-analysis, it showed that IL10 rs1800896 and rs1800871 polymorphisms had no association with breast cancer risk, while rs1800872 polymorphism had a decreased risk of breast cancer in Caucasians [3]. However, another meta-analysis suggests that IL10 rs1800871 and rs1800872 polymorphisms might contribute to breast cancer susceptibility in the overall population, but not by ethnicity [6].…”
Section: Diseasementioning
confidence: 99%
“…It presents polymorphisms (SNPs), most of them within the promoter regions, and has been proposed as responsible for the altered function, by dysregulating their expression. Several groups report associations between polymorphism and cancer risk [3][4][5][6][7]. It is a helical cytokine and exists in solution predominantly as a homodimer, composed of two polypeptide chains of 160 amino acids, each with a molecular weight of 20,6419 kD [8].…”
Section: Interleukin 10 (Il-10)mentioning
confidence: 99%